Opening Remarks from the 2022 Symposium: The Equal Rights Amendment: A New Guarantee of Sex Equality in the U.S. Constitution - Jaffe-Geffner, Nina (Columbia Journal of Gender and Law, 2022)
Ms. Jaffe-Geffner’s remarks were delivered at the 2022 Symposium The Equal Rights Amendment: A New Guarantee of Sex Equality in the U.S. Constitution. The event was co-sponsored by the Columbia Journal of Gender and Law and the Columbia Law School ERA Project.